2001
DOI: 10.1017/s1092852900022045
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Clinical Communication in Schizophrenia: The Approaches to Schizophrenia Communication Checklists

Abstract: Side effects from antipsychotic medications can have a profound effect on patients' lives and may adversely affect their willingness to comply with treatment. Identification of side effects through improved communication between psychiatrists, other members of the healthcare team, and their patients might increase treatment compliance. The Approaches to Schizophrenia Communication (ASC) Steering Group developed two simple, practical checklists for use in the busy clinical setting. The ASC–Self-Report (ASC-SR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 11 publications
0
45
0
Order By: Relevance
“…This review identified six SRQs currently available that can be used in the assessment of mental health patients' subjective experiences of medication side effects (Day et al, 1995;Dott et al, 2001;Lindstrom et al, 2001;Wolters et al, 2006;Waddell and Taylor, 2008;Mojtabai et al, 2012). An evaluation of the characteristics of each study is shown in Table 1.…”
Section: Aims 1 and 2 (Identified Srqs And Study Characteristics)mentioning
confidence: 99%
See 2 more Smart Citations
“…This review identified six SRQs currently available that can be used in the assessment of mental health patients' subjective experiences of medication side effects (Day et al, 1995;Dott et al, 2001;Lindstrom et al, 2001;Wolters et al, 2006;Waddell and Taylor, 2008;Mojtabai et al, 2012). An evaluation of the characteristics of each study is shown in Table 1.…”
Section: Aims 1 and 2 (Identified Srqs And Study Characteristics)mentioning
confidence: 99%
“…There was significant variation between studies in terms of design, duration, validation methods and outcomes. There were three longitudinal studies (Day et al, 1995;Wolters et al, 2006;Waddell and Taylor, 2008), one prevalence study (Lindstrom et al, 2001), a cross sectional (Mojtabai et al, 2012) and a pilot study (Dott et al, 2001). Sample sizes varied from 50 to 320 patients, and settings varied from patients' homes to clinics.…”
Section: Aims 1 and 2 (Identified Srqs And Study Characteristics)mentioning
confidence: 99%
See 1 more Smart Citation
“…The proportions of people reaching threshold scores for possible mental ill health were to be compared. l The Antipsychotic Side-effect Checklist (ASC) 48 was used to measure adverse effects of psychotropic medication. The ASC comprises a list of the more common or clinically important side effects of antipsychotic treatment.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%
“…However, mental health consumers often experience difficulties in communicating openly with clinicians, possibly because they may be reluctant to fully disclose their personal circumstances, or the medication or the illness has journey for many mental health consumers (Dassori et al, 2003;De Leeuw et al, 2012;Dott et al, 2001).…”
Section: Introductionmentioning
confidence: 99%